PERHITUNGAN BEBAN MODAL MINIMUM DENGAN PENDEKATAN Advanced Internal Rating Based (AIRB) MODEL Loss Given Default (LGD) - , Nur Arina Hidayati ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The Calculation of minimum capital charges with LGD model of AIRB approach is one of ways to calculate the credit risk weight, a part of bank's efforts in managing the risks occurred because of defaulted debtors. In the AIRB approach, it is required components risks required to calculate the minimum capital charges, namely Probability of Default (PD), Loss Given Default (LGD), Maturity (M). In addition, this model is also needed other risk components, namely: Conditional Probability of Default (CPD), Conditional Loss Given Default (CLGD) and Maturity Adjustment (MatAd). CLGD is a form of LGD modeling where the CLGD formulation formed by using beta distribution.